2021
DOI: 10.3390/genes13010100
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the Wheat Cultivar ‘Renan’ to Septoria Leaf Blotch Explained by a Combination of Strain Specific and Strain Non-Specific QTL Mapped on an Ultra-Dense Genetic Map

Abstract: Quantitative resistance is considered more durable than qualitative resistance as it does not involve major resistance genes that can be easily overcome by pathogen populations, but rather a combination of genes with a lower individual effect. This durability means that quantitative resistance could be an interesting tool for breeding crops that would not systematically require phytosanitary products. Quantitative resistance has yet to reveal all of its intricacies. Here, we delve into the case of the wheat/Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 92 publications
(148 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, it has been suggested that the removal of highly distorted SNPs or bins during the construction of genetic maps is responsible for fragmentation of the chromosomes ( Gong et al, 2020 ). This was also found in wheat, where a recent ultra-dense genetic map yielded 25 linkage groups for the 21 chromosomes of this crop ( Langlands-Perry et al, 2021 ). Importantly, although the chromosomes in our linkage map are fragmented into subgroups, this does not restrict the use of our linkage map, whose quality was verified by several independent controls.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, it has been suggested that the removal of highly distorted SNPs or bins during the construction of genetic maps is responsible for fragmentation of the chromosomes ( Gong et al, 2020 ). This was also found in wheat, where a recent ultra-dense genetic map yielded 25 linkage groups for the 21 chromosomes of this crop ( Langlands-Perry et al, 2021 ). Importantly, although the chromosomes in our linkage map are fragmented into subgroups, this does not restrict the use of our linkage map, whose quality was verified by several independent controls.…”
Section: Discussionmentioning
confidence: 58%
“…The 13 QTLs identified in this study were compared to over 100 QTLs from six GWAS studies, studies using segregating populations and 24 named Z. tritici genes (Aouini 2018; Langlands-Perry et al 2022; Tabib Ghaffary et al 2018; Yang et al 2018). Firstly, genomic DNA sequences of the 13 QTLs based on the confidence intervals were extracted from the IWGSC RefSeq v1.0 (https://urgi.versailles.inra.fr/).…”
Section: Methodsmentioning
confidence: 99%
“…The 13 QTLs identified in this study were compared to over 100 QTLs from six GWAS studies, studies using segregating populations and 24 named Z. tritici genes (Aouini 2018;Langlands-Perry et al 2022;Tabib Ghaffary et al 2018;Yang et al 2018)…”
Section: Bioinformatic Analysismentioning
confidence: 99%
See 2 more Smart Citations